2021
DOI: 10.1002/adfm.202101255
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry‐Broken Au–Cu Heterostructures and their Tandem Catalysis Process in Electrochemical CO2 Reduction

Abstract: Symmetry-breaking synthesis of colloidal nanocrystals with desired structures and properties has aroused widespread interest in various fields, but the lack of robust synthetic protocols and the complex growth kinetics limit their practical applications. Herein, a general strategy is developed to synthesize the Au-Cu Janus nanocrystals (JNCs) through the site-selective growth of Cu nanodomains on Au nanocrystals, which is directed by the substantial lattice mismatch between them, with the assistance of judicio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 77 publications
0
58
0
Order By: Relevance
“…We note here that it is unlikely that *OH actually binds to roughened Cu under CO2RR conditions, as it would have a very strong driving force to reduce to water; rather, ΔΩ OH serves as a descriptor for the formation of formate. Competition between formate and the C 1+ pathway highlight the success of tandem catalysis: by utilizing a catalyst such as Ag which selectively reduces CO 2 to CO which then diffuses to Cu, the formate pathway is partially eliminated.…”
mentioning
confidence: 99%
“…We note here that it is unlikely that *OH actually binds to roughened Cu under CO2RR conditions, as it would have a very strong driving force to reduce to water; rather, ΔΩ OH serves as a descriptor for the formation of formate. Competition between formate and the C 1+ pathway highlight the success of tandem catalysis: by utilizing a catalyst such as Ag which selectively reduces CO 2 to CO which then diffuses to Cu, the formate pathway is partially eliminated.…”
mentioning
confidence: 99%
“…The potential of heterodimeric NPs as catalysts was revealed through the study of Au–Cu NPs for electrocatalytic reduction of CO 2 . Cu NPs have shown great promise as an electrocatalyst for CO 2 reduction, but poor selectivity persists. , To address this challenge, heterodimeric Au–Cu NPs were synthesized by overgrowth of Cu from bipyramidal Au seeds, where the large lattice mismatch between Au and Cu facilitated dimer formation (Figure A,B) . Au–Cu heterodimers from spherical Au seeds, core@shell Au@Cu NPs, Au nanobipyramids, Cu nanospheres, and mixtures of the two were also synthesized for comparison.…”
Section: Catalytic Propertiesmentioning
confidence: 99%
“…Typically, symmetry reduction is achieved during seed-mediated methods where there is a large lattice mismatch between the seeds and depositing material, the supply of depositing atoms is low (i.e., low supersaturation), nanocrystal surfaces (or seeds) are asymmetrically passivated, or seeds are confined at interfaces . Symmetry-reduced NPs prepared by these methods are proving useful for applications ranging from security devices to electrocatalysts. …”
Section: Introductionmentioning
confidence: 99%
“…[16a] However, to the best of our knowledge, limited research progress has been achieved in the case of Au-Cu combination. [17] Although the large lattice mismatch exists between the two metals, most Au-Cu products documented in literature adopted the core-shell or alloy structure. [18] We also noted that some of the previous studies reported the successful asymmetric growth observed in the synthesis of Au-Cu nanocrystals.…”
Section: Introductionmentioning
confidence: 99%